Village Regeneration and NRRP. Tourism Development Perspectives in the Post Covid Era: English - Tocci, Giovanni (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2024)
In the aftermath of the pandemic emergency, the emphasis on remote work, social distancing, and travel restrictions has significantly changed social and work habits. As a result, the concept of rural areas and villages is no longer viewed as vacation destinations only, but as places for new lifestyle choices considering the increased security, well-being, and larger living spaces available. Italy is the country of small municipalities and this widespread distribution of small towns provides many opportunities in terms of development. Indeed, these places may be potentially able to generate a more human-scale economy relying on communities and territories, the interplay of innovation and local “knowledge”, traditions, food and wine, and typical products. These factors may leverage the rebirth of the whole tourism sector in the post-Covid era. This paper examines sustainable tourism as a tool for the development of territories by focusing on food, sustainability, and tourism in small centers and local contexts. Within the re-shaped framework set by the pandemic, support measures and interventions provided by the National Recovery and Resilience Plan (NRRP) to enhance the attractiveness of villages are investigated. Specifically, this work delves into the innovative steps, taken by some small municipalities which have benefited from the Plan’s funds, towards the development and improvement of virtuous models of growth and residents’ well-being, thanks to the promotion of sustainable and quality tourism. The study aims to identify modalities for the enhancement of territories and the revamp of places, with a specific focus on the ability of NRRP-funded strategies to improve the quality of life and concretely generate social innovation.